Play-Based Learning With Games as a Dance Teaching Tool - Azmi, Nurafiqah Diyanah; Ha, Sang Woo (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2024)
This case study focuses on Play-based Learning with game elements as a new dance teaching tool for young children. The research objective is to verify that the majority of games used by teachers in Malaysian preschools are based on guided play, which includes adults’ guidance and mentoring on a play, and that each game is designed to improve students’ cognitive and psychomotor development, social abilities, and academic skills. Researchers also emphasize that Play-based Learning with game elements can be used as a new teaching method of dance for young children who cannot follow teaching contents. To achieve these objectives, researchers discuss how games are used as a teaching method by two different preschools, investigate how these games are suitable for all students aged 4 to 6 years old, and examine the effect of games as teaching tools in Music and Movement classes. Utilizing the qualitative methodology, researchers interviewed teachers to investigate how teachers incorporate games in Music and Movement classes. Researchers conducted participant observation in Music and Movement classes to identify whether or not the use of games in this case study belongs to free play or guided play. Researchers also gathered information through secondary written sources. The findings suggest that games as a teaching method in Music and Movement classes greatly emphasize students learning how to dance, where games create more excitement for the children and not worry too much about techniques. Games used by Malaysian preschools can be great examples and guidelines for teachers to incorporate games as a teaching method for preschool students aged 4 to 6 years old.